Luncheon for Attorney General Edmund G. "Pat" Brown Candidate for Governor
Ticket for a luncheon for Attorney General Edmund G. "Pat" Brown Candidate for Governor Luncheon at Kit's Palomino Room, Oxnard, CA. Date not provided. Circa 1959.